Mutation analysis of the TERT gene in ovarian cancer patients of the Turkish population by next generation sequencing method: Analysis of the TERT in ovarian cancer by NGS - Capar Gorali, Betul; Gulec Yılmaz, Seda; Akdeniz, Fatma Tuba; Attar, Rukset; İsbir, Turgay (Cellular and Molecular Biology, 2023)
Ovarian cancer (OC) ranks seventh among malignant tumors worldwide. As one of the most common gynecological malignancies, ovarian cancer has the second-highest mortality rate, after cervical and uterine cancer. Next-Generation Sequencing (NGS) technology has enhanced multi-gene panel analysis and its clinical utility for identifying cancer-causing gene mutations. This study aimed to determine the presence of significant and nonsense mutations in telomerase reverse transcriptase (TERT), alpha-thalassemia/mental retardation, X-linked (ATRX), O-6-methylguanine-DNA methyltransferase (MGMT), and isocitrate dehydrogenase 1 and 2 (IDH1/IDH2) genes using the Next-Generation Sequencing (NGS) method. A cohort of 33 patients diagnosed with ovarian cancer was included in this investigation, and peripheral blood samples were collected from all participants. Significant and nonsense mutations in TERT, ATRX, MGMT, IDH1, and IDH2 genes were detected using the Next-Generation Sequencing method. Bioinformatics analysis was conducted using the QIAGEN Clinical Insight system. Twenty-four patients exhibited seven different TERT mutations, occurring in both exonic and intronic regions. One patient displayed a c.699-3delC deletion in the intronic region of the IDH1 gene, and the c.532G > A (p.V178I) mutation observed in three patients was assessed as potentially harmful. Additionally, novel mutations c.881A > G and c.995A > G were observed in the ATRX gene. The heterozygous novel mutation identified in the ATRX gene was confirmed through Sanger sequencing. These mutations were not previously associated with ovarian cancer and are considered novel candidate markers for ovarian cancer susceptibility. Confirmation of these results through larger cohort studies or functional investigations will contribute to a better understanding of the molecular mechanisms underlying ovarian cancer.